Factors Affecting Voluntary Self-Isolation Behavior to Cope with a Pandemic: Empirical Evidence from Colombia vs. Spain in Times of COVID-19 (2021)
Global pandemics are not a new phenomenon. They have occurred at different points in time and can be of different scales. COVID-19 appeared in 2020 and its spread has reached more than 60 countries worldwide. This research aims to analyze voluntary self-isolation behavior used to cope with the COVID-19 pandemic. As part of this study, we carried out sampling in Colombia and Spain, which share similar cultural characteristics but which have substantial social and economic differences. A multi-group model was used to test the application of the theory of planned behavior and the theory of reasoned action in order to analyze self-isolation behavior. The results show that there are differences in self-isolation behavior between both countries, especially with regard to attitudes towards self-isolation and volitional behavior